Katherine Mansfield and Virginia Woolf - Froula, Christine, 1950-; Kimber, Gerri; Martin, W. Todd (Katherine Mansfield studies, 2018)
These comparative essays explore the shared terrain of these modernist women writers and shed new light on their'curious & thrilling' literary relationship.